Studi Deskriptif Tentang Indeks Massa Tubuh (IMT), Lingkar Pinggang dan Tekanan Darah pada Mahasiswa/I Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sriwijaya - Utami, Anggun Fitri; Wardiansah (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Background. Body mass index (BMI) is a measurement indicator recommended by WHO to identify the nutritional status of an individual. Measurement of BMI can’t identify the location of distribution of intraabdominal fat (visceral fat) so waist circumference is necessary. Individuals with BMI values that exceed normal values and large intraabdominal fat distribution will cause a physiological adaptation in the body in the form of an increase in blood volume which will cause an increase in blood pressure. Measurement of BMI, waist circumference and blood pressure need to be done as an early detection considering that students have a high enough risk to suffer from obesity and hypertension. Methods. This research was an observational descriptive study with a cross sectional design. Sampling is done by total sampling. Body weight and height measurements were taken to calculate the value of body mass index (BMI), measurement of waist circumference and measurement of blood pressure on students at the Faculty of Medicine Universitas Sriwijaya class of 2016. The collected data were presented in table and percentage form. Result. The value of BMI in the category of overweight and obesity is most at the age of 20-21 years (20.6%) and in female (14%). The value of waist circumference in the abnormal category is most at the age of 20-21 years in men (5.3%) and women (11.81%). The value of blood pressure that has pre-hypertension and first degree hypertension is in students aged 20-21 years (20.2%) and most in men (14%). The blood pressure values included in the pre-hypertension and first-degree hypertension categories were most on the BMI values in the overweight and obese categories (18.8%) and in the waist circumference in the medium and large categories (13.81%). Conclusion. The distribution of research subjects based on BMI and waist circumference that exceeds the normal value is most at the age of 20-21 years and in women. The distribution of research subjects based on blood pressure that experienced pre-hypertension and first degree hypertension was most at the age of 20-21 years and in men. The distribution of research subjects based on blood pressure that experienced pre-hypertension and first degree hypertension at most in the value of BMI and waist circumference that exceeds the normal value.